Analisis Dampak Human Error Terhadap Kebocoran Data Pribadi di Kalangan Pengguna Digital - Dian Humaira; Nur Aza Fazlasya; Sadhi Alwi; Putra Harapan Tafonao (JIKUM: Jurnal Ilmu Komputer, 2026)
The rapid development of digital technology has increased the risk of personal data leakage, which is often caused by human error rather than system technical failures. This study aims to analyze the impact of human error, such as the use of weak passwords, clicking on phishing links, and sharing excessive information on social media, on the security of personal data. The research method used is a qualitative approach through literature review and analysis of recent data leakage cases. The results indicate that low digital literacy is the main factor contributing to human error. This study concludes that an increase in digital security awareness and education is essential to minimize the risk of data leakage caused by human factors.